Dinamika Kecerdasan Emosional Peserta Didik dalam Situasi Fatherless - Zakia, Rahima; Solina, Wira; Putra, Fuaddillah (Kartika: Jurnal Studi Keislaman, 2025)
This study is motivated by the condition of students who rarely spend time with their fathers, lack affection, and often feel sad when seeing their peers accompanied by their fathers. Such fatherless situations create specific dynamics in the development of students’ emotional intelligence. The purpose of this research is to describe the phenomenon of fatherlessness, map the level of emotional intelligence, and identify the relationship between the two among eighth-grade students at SMP N 27 Padang. A quantitative approach was employed, with a population of 200 students and a randomly selected sample of 70 students. Data were collected using a questionnaire and analyzed through simple linear regression to support the mapping of conditions. The findings reveal that students’ fatherlessness is categorized as high, while their emotional intelligence is classified as very high. These results indicate that despite experiencing fatherless conditions, most students are able to demonstrate strong emotional regulation, empathy, and social skills. The study highlights the importance of special attention from guidance and counseling teachers, subject teachers, and parents in strengthening students’ emotional intelligence by fostering a supportive and collaborative school environment.